Interfacial modified unidirectional wheat straw/polylactic acid composites. Issue 1 (June 2022) - Li, Wuzhou; Zheng, Liangang; Teng, Defang; Ge, Dongsheng; Farha, Farial I; Xu, Fujun
Among the agricultural crops, wheat is one of the most important and broadly planted food crops. However, abundant wheat straw resources were used to incinerate, which was a great waste of fiber resources, and meanwhile caused great pollution to the ecological environment. In this work, a simple hot compress method that used intact wheat straw with different volume fractions (20% and 30%) as a filler to reinforce the polylactic acid resin was explored to prepare a biodegradable composite by thermal compression method. Initially, the compressed wheat straw exhibited excellent tensile strength (96.86 MPa), even higher than intact wheat straw (92.18 MPa). The surface modification treatment was carried out with 2% and 4% concentrations of sodium hydroxide (NaOH). Then the tensile and bending strength of the modified wheat straw/polylactic acid composites were 32.41 MPa and 78.52 MPa, which were 22.16% and 22.44% higher than those of the untreated composites. The scanning electron microscopy images of the surface of modified wheat straw and fractured composite cross section revealed significantly rougher surface morphology and stronger interfacial bonding with the matrix. This work demonstrated the feasibility and good mechanical property of the composites reinforced with intact wheat straw by simple hot compression method, which provided a possible strategy to utilize the straw materials for multiple applications.